2023
DOI: 10.1101/2023.01.04.522794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targets and cross-reactivity of human T cell recognition of Common Cold Coronaviruses

Abstract: The Coronavirus (CoV) family includes a variety of viruses able to infect humans. Endemic CoVs that can cause common cold belong to the alphaCoV and betaCoV genera, with the betaCoV genus also containing subgenera with zoonotic and pandemic concern, including sarbecoCoV (SARS-CoV and SARS-CoV-2) and merbecoCoV (MERS-CoV). It is therefore warranted to explore pan-CoV vaccine concepts, to provide adaptive immune protection against new potential CoV outbreaks, particularly in the context of betaCoV sub lineages. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Thus, even though we cannot unequivocally claim that such multi-specific T cell responses demonstrate previous infection by SARS-CoV-2, it is essential to highlight that the cross-reactive T cells found in 30% to 70% of individuals tested before the pandemic ( 24 , 25 ) were limited to single SARS-CoV-2 proteins ( 22 ). In addition, recent work showed that the CD4 + T cell response induced by NL-63 and OC-43 coronavirus infections largely do not overlap with SARS-CoV-2–induced CD4 + T cells ( 35 ). Therefore, we conclude that the detection of T cells specific for different SARS-CoV-2 proteins in the same individual is highly indicative of previous asymptomatic SARS-CoV-2 infection, as shown in seronegative health care workers in the United Kingdom who had been exposed to the virus ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even though we cannot unequivocally claim that such multi-specific T cell responses demonstrate previous infection by SARS-CoV-2, it is essential to highlight that the cross-reactive T cells found in 30% to 70% of individuals tested before the pandemic ( 24 , 25 ) were limited to single SARS-CoV-2 proteins ( 22 ). In addition, recent work showed that the CD4 + T cell response induced by NL-63 and OC-43 coronavirus infections largely do not overlap with SARS-CoV-2–induced CD4 + T cells ( 35 ). Therefore, we conclude that the detection of T cells specific for different SARS-CoV-2 proteins in the same individual is highly indicative of previous asymptomatic SARS-CoV-2 infection, as shown in seronegative health care workers in the United Kingdom who had been exposed to the virus ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + T cells have the tremendous advantage to be able to cross-react with similar or distinct peptides, and in the context of viral mutation, this aids in limiting viral escape ( Augusto et al, 2023 ; Kundu et al, 2022 ; Lineburg et al, 2021 ; Gras et al, 2010 ; Grant et al, 2018 ; Tarke et al, 2023 ; Loyal et al, 2021 ; Richards et al, 2015 ). To take advantage of the T cell's ability to engage and recognise multiple variants, we need to better understand the landscape of antigen presentation and the impact of peptide mutation on HLA presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, T cells can oftentimes recognise variations in peptide antigens, and this is referred to as T cell cross-reactivity, further increasing the number of peptides under T cell surveillance from each individual ( Sewell, 2012 ). This is particularly important in the case of viral mutation, where T cells can cross-recognise multiple variants of a virus ( Augusto et al, 2023 ; Kundu et al, 2022 ; Lineburg et al, 2021 ; Gras et al, 2010 ; Grant et al, 2018 ; Tarke et al, 2023 ; Loyal et al, 2021 ; Richards et al, 2015 ). However, currently there is a limited knowledge on antigen-specific T cell responses towards SARS-CoV-2 virus, and our work could provide foundational information to develop new therapeutics, especially against emerging variants.…”
Section: Introductionmentioning
confidence: 99%
“…However, MPs designed with overlapping peptides spanning an individual antigen or a combination of several could be initially used to screen for donor responsiveness, further introduced into an epitope screening pipeline, and sequentially deconvoluted to map CD4+ T cell reactivity for individual peptides. This multi‐step approach has been recently employed for genome‐wide screening and epitope identification for SARS‐CoV‐2, common cold coronaviruses, and Bordetella pertussis (da Silva Antunes et al., 2023; Tarke, Sidney, Kidd, et al., 2021; Tarke et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Additional MPs were subsequently generated, based on experimentally defined epitopes, and used to derive immunodiagnostic strategies to address vaccination and infection history (Grifoni et al., 2021; Tarke, Sidney, Kidd, et al., 2021; Yu, Wang, Garrigan, Goodwin, et al., 2022). In parallel, specific MPs were also derived to follow responses to other coronavirus species, such as the main common cold coronaviruses (da Silva Antunes, Pallikkuth, et al., 2021; Tarke et al., 2023; Yu, Narowski, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%